Influence of natural antifungal coatings produced by Lacto-fermented antifungal substances on respiration, quality, antioxidant attributes, and shelf life of mango (Mangifera indica L.) - Ranjith, Fernando H.; Ariffin, Siti Hajar; Muhialdin, Belal J.; Yusof, Noor Liyana; Mohammed, Nameer K.; Marzlan, Anis Asyila; Meor Hussin, Anis Shobirin (Elsevier, 2022)
Active coating systems are a promising postharvest strategy for managing quality attributes while controlling postharvest diseases of fresh fruit. This work aims to determine the respiration, quality, antioxidant attributes, and shelf life of fresh mango treated with different natural antifungal coatings produced by Lacto-fermented antifungal compounds. The respiration rates were modeled using the uncompetitive Michaelis-Menten model. Mango samples were coated with five different antifungal coating solutions: negative control (immersed in distilled water), positive control (coated with chitosan (CH)+Benomyl), coated with CH+antifungal substances produced by Lactobacillus plantarum ATCC8014 in palm kernel cake (PKCL1), and CH+antifungal substances produced by Lactobacillus fermentum ATCC9338 in palm kernel cake (PKCL2), and coated with pure CH and stored at 25 ± 2 °C. Mango samples treated with CH+Benomyl and CH+PKCL2 had a shelf life of up to 18 days, whereas CH+PKCL1, pure CH coated, and negative control samples had shelf lives of 17, 14, and 9 days, respectively. The difference in O2 and CO2 concentrations were not significant among coated samples, but they were significant between coated samples and the uncoated negative control. The uncompetitive Michaelis-Menten model exhibited good agreement with the respiration rates of fresh mango, and it was confirmed to have a good fit to explain the results such as quality, antioxidants, and shelf life in the study. Weight loss, color, flesh firmness, ascorbic acid (AA) content, and antioxidant properties were not significantly different among coating treatments, although they differed significantly between coated and uncoated negative controls. CH+PKCL2 was the best antifungal coating formulation to preserve fresh mango. It has performed similarly to the antifungal coating prepared by a commercial fungicide, Benomyl.